Alliances and Co-Evolution Insights from the Banking Sector - ul-Haq, R. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2005)
Alliances and Co-Evolution provides alliance managers, consultants and academics with a detailed analysis covering 23 years of the growth and decline of three lifecycles of alliances. This analysis links structural change in the European macro-environment with corporate alliance strategies. It differentiates between strategic alliances and infrastructure alliances with their differing strategic drivers, and proposes a Co-Evolution model to explain, monitor and manage the development of alliances over time.